Stratergi Pembelajaran Edutaiment Dalam Pembelajaran - Rizka Zulmi; Karlina Putri; Gusmaneli Gusmaneli (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The use of learning strategies that combine aspects of entertainment is known as "edutainment" or entertainment education. This strategy aims to make the learning process more interesting and enjoyable, thereby increasing student motivation and involvement. Implementing this edutainment strategy not only makes learning more enjoyable, but can also improve students' knowledge retention, critical thinking skills and collaboration abilities. In the edutainment concept, the essence of the learning process is to create a pleasant, comfortable and amazing atmosphere, thereby facilitating the formation of a harmonious and dynamic relationship between teachers and students. Through a pedagogical dedactic approach with redagonistic nuances, the interactions that occur between teachers and students become not only effective but also relaxed and free, allowing students to interact without fear or limitations. This is very important because when students feel comfortable with their learning environment, they are more likely to actively engage and acquire knowledge in a more effective and enjoyable way. In implementing edutainment learning strategies, there are certainly advantages and disadvantages, but this is something that is common in every learning strategy. Because learning strategies are applied not to be forced but according to the needs of the ongoing learning process.